Virtual humans : back to the future - Thalmann, Nadia Magnenat (2013)
This paper essentially tries to examine all the roles that Virtual Humans can play in empowering human expression, and the research challenges we have to face to make this possible. It starts with a short history of Virtual Humans and how we contribute to the foundations of this field. We then define six typical Virtual Humans: the Performing Virtual Human, the Physiological Virtual Human, the Learning Virtual Human, the Connected Virtual Human, the Secure Virtual Human, and the Anthropometric Virtual Human. For each category, we provide a definition and a few possible scenarios, then we try to identify the research challenges, the past experiences, and some unsolved core issues.